Low-carrier oxyhalide solid electrolyte material and preparation method thereof

By using oxides of positive tetravalent or above transition metals as host structures in inorganic solid electrolytes and filling them with corresponding halides, the low-carrier oxygen halide solid electrolyte materials are prepared, and the problems of high carrier dependence and low ionic conductivity in the prior art are solved, and efficient battery performance and safety improvements are achieved.

CN119812450AActive Publication Date: 2025-04-11TIANJIN UNIV

Patent Information

Application Number
CN202510016230.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

In practical applications, existing inorganic solid electrolytes face problems such as high carrier dependence, low ionic conductivity, poor interface stability and poor physical and mechanical stability, which affect the performance and safety of the battery.

Method used

Low carrier oxygen halide solid electrolyte material is prepared by selecting oxides of transition metals of positive tetravalent or above as the host structure and filling them with halides of transition metals of positive tetravalent or above and alkali metals. The raw materials of this material are evenly mixed by mechanical ball milling to ensure good interface compatibility between the materials, form a crystal structure the same as the host structure, and improve ionic conductivity.

Benefits of technology

It realizes that while reducing carrier usage, the charging and discharging efficiency and cycle stability of the battery are improved, the safety and economy of the battery are improved, and the problems of flammability and low energy density of traditional liquid batteries are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005230005360000111
    Figure BDA0005230005360000111
  • Figure BDA0005230005360000121
    Figure BDA0005230005360000121
  • Figure HDA0005230005380000011
    Figure HDA0005230005380000011
Patent Text Reader

Abstract

The invention provides a low-carrier oxyhalide solid electrolyte material and a preparation method thereof. The low-carrier oxyhalide solid electrolyte material provided by the invention has a general formula of AaMbOBc, wherein a is more than 0.3 and less than 0.7, b is more than 0.35 and less than 1.1, and c is more than 1 and less than 4; the material is prepared from the following raw materials: transition metal oxide Mz1Oz2 serving as a host structure, alkali metal halide Ax1Bx2 serving as filler and transition metal halide My1By2, the material AaMbOBc and the host structure Mz1Oz2 have the same crystal structure; and the consistency of the crystal structure is beneficial to high-efficiency transmission by using fewer current carriers, so that the purpose of improving the ionic conductivity is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a low-carrier oxyhalide solid electrolyte material and a preparation method thereof. Background Art

[0002] Traditional liquid ion batteries have high safety risks due to the use of flammable organic liquid electrolytes. In addition, the energy density of traditional liquid ion batteries is already close to its theoretical value, making it difficult to further improve it. Therefore, there is an urgent need to develop a new energy storage system with high safety and high energy density.

[0003] Developing inorganic solid electrolytes and matching them with high-energy-density metal negative electrodes can achieve high energy density and solve the flammability problem of traditional liquid batteries. The research on inorganic solid electrolytes is currently focused on materials such as oxides, sulfides and halides; among them, halide solid electrolytes are a kind of superionic conductor composed of halogen elements as anions and metal elements as central metal cations; halide solid electrolytes have higher ion conductivity and excellent deformability than oxides; compared with sulfide solid electrolytes, they have excellent oxidation stability and good water / air stability, so they are considered to have good commercial prospects.

[0004] However, despite the above advantages of inorganic solid electrolytes, they still face some challenges in practical applications. Whether it is oxides, sulfides or halides, inorganic solid electrolytes require a large amount of carriers such as lithium and sodium to maintain the crystal structure and maintain high ion conductivity; this not only increases the cost of materials, but also poses a challenge to the sustainable use of resources. In addition, the ionic conductivity of inorganic solid electrolytes is usually lower than that of liquid electrolytes, which limits their charging and discharging speed and battery rate performance. At the same time, the interface stability between inorganic solid electrolytes and electrode materials is a challenge. Poor physical and mechanical stability may cause structural stress at the electrode / electrolyte interface, affecting the electrochemical performance of the battery. Therefore, how to study and optimize an inorganic solid electrolyte material can reduce dependence on expensive metal resources such as lithium while improving battery performance, and improve battery safety and economy, which is of great significance to promote the development and commercialization of solid-state battery technology. Summary of the invention

[0005] The present invention aims at solving the problems in the prior art and discloses a low-carrier oxyhalide solid electrolyte material and a preparation method thereof. The low-carrier oxyhalide solid electrolyte material provided by the present invention comprises a transition metal oxide M as a host structure. z1 O z2 , alkali metal halide A as filler x1 B x2and transition metal halide M y1 B y2 ; Material A a M b OB c and the host structure M z1 O z2 Having the same crystal structure; the consistency of the crystal structure helps to efficiently transmit with fewer carriers, thereby achieving the purpose of improving ion conductivity.

[0006] The present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a low-carrier oxyhalide solid electrolyte material; the material has the general formula: A a M b OB c ;0.3<a<0.7, 0.35<b<1.1, 1<c<4;

[0008] The raw materials of the material include transition metal oxide M as a host structure z1 O z2 , alkali metal halide A as filler x1 B x2 and transition metal halide M y1 B y2 ; Material A a M b OB c and the host structure M z1 O z2 have the same crystal structure;

[0009] Among them, the alkali metal A includes one or more of lithium (Li), sodium (Na), and potassium (K); M includes transition metal elements with a valence of four or more; the halogen atom B includes one or more of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); the transition metal elements with a valence of four or more include one or more of titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), hafnium (Hf), zirconium (Zr), cobalt (Co), nickel (Ni), tantalum (Ta), tungsten (W), rhenium (Re), vanadium (V), niobium (Nb), and tin (Sn).

[0010] As a further embodiment, the A x1 B x2 、M z1 O z2 and M y1 B y2 In, x 1 、x 2 ,y 1,y 2 、z 1 、z 2 All are greater than 0; x 1 =x 2 .

[0011] As a further embodiment, the material A a M b OB c Preferably 1.2<b / a<2;

[0012] Furthermore, the material A a M b OB c Preferably, it is selected from the group consisting of 0.5<a<0.6, 0.75<b<0.88, 2<c<3.5, and 1.45<b / a<1.65.

[0013] As a further embodiment, the transition metal oxide M z1 O z2 Preferred are oxides of transition metal elements containing positive pentavalent valence.

[0014] As a further embodiment, the transition metal oxide M z1 O z2 Preferred from Ta 2 O 5 , Nb 2 O 5 One or more of; the alkali metal halide A as filler x1 B x2 Preferably, one or more of LiCl, LiF, NaCl, and LiBr; the transition metal halide M as the filler y1 B y2 Preferably TaCl 5 、NbCl 5 、TaBr 5 , NbBr 5 One or more of .

[0015] As a further solution, the low-carrier oxyhalide solid electrolyte material is selected from Li 0.53 Nb 0.4 Ta 0.4 OCl 2.53 , Li 0.53 Ta 0.8 OCl 2 Br 0.53 , Li 0.42 Ta 0.32 Zr 0.32 OCl 1.26 , Li 0.66 Ta 0.5 Zr0.5 OCl 3.16 、That 0.6 TaOCl 3.79 、That 0.405 Of 0.5 OCl 1.9 、That 0.325 Of 0.6 OCl 1.325 、That 0.56 Of 0.8 OCl 2.56 、That 0.4 Of 0.7 OCl 1.9 、That 0.53 Of 0.8 OCl 1.32 、That 0.53 Of 0.8 OCl 2.53 、That 0.53 Nb 0.8 OCl 2.53 、That 0.53 Zr 0.8 OCl 2.53 、That 0.66 Of 0.5 Sn 0.5 OCl 3.16 、No 0.53 Of 0.8 OCl 2.53 、No 0.53 Nb 0.8 OCl 2.53 、No 0.53 Zr 0.8 OCl 2.53 、K 0.53 Of 0.8 OCl 2.53 、K 0.53 Nb 0.8 OCl 2.53 、K 0.53 Zr 0.8 OCl 2.53 、That 0.53 Of 0.8 OClF 2.53 、That 0.53 Nb 0.8 OClF 2.53 、That 0.53 Zr 0.8 OClF 2.53 、No 0.53 Of 0.8 OClF 2.53 、No 0.53 Nb 0.8OClF 2.53 、Na 0.53 Zr 0.8 OClF 2.53 , K 0.53 Ta 0.8 OF 2.53 , K 0.53 Nb 0.8 OF 2.53 , K 0.53 Zr 0.8 OF 2.53 , Li 0.53 Ta 0.8 OBr 2.53 , Li 0.53 Nb 0.8 OBr 2.53 , Li 0.53 Zr 0.8 OBr 2.53 、Na 0.53 Ta 0.8 OBr 2.53 、Na 0.53 Nb 0.8 OBr 2.53 、Na 0.53 Zr 0.8 OBr 2.53 , K 0.53 Ta 0.8 OBr 2.53 , K 0.53 Nb 0.8 OBr 2.53 , K 0.53 Zr 0.8 OBr 2.53 One of them.

[0016] As a further embodiment, the transition metal M is preferably selected from one or more of niobium (Nb) and tantalum (Ta).

[0017] As a further embodiment, the alkali metal A is preferably selected from lithium (Li) ions.

[0018] As a further embodiment, the halogen atom B is preferably one or more selected from Cl and Br.

[0019] As a further embodiment, the material A a M b OB c Preferred from Li a Ta b OCl c , Li a Nb b OCl c , Li a Tab OBr c , Li a Nb b OBr c One or more of; wherein, 0.3<a<0.7, 0.35<b<1.1, 1<c<4, 1.2<b / a<2.

[0020] As a further embodiment, the ionic conductivity of the material is greater than 1 mS cm -1 .

[0021] As a further solution, the mass percentage of A atoms in the material is selected from 1-3%, wherein the mass percentage refers to the total mass of A atoms in the material A. a M b OB c Ratio of total mass.

[0022] Furthermore, the mass percentage of A atoms in the material is preferably 1-1.5%.

[0023] In a second aspect, the present invention provides a method for preparing a low-carrier oxyhalide solid electrolyte material; the preparation method comprises:

[0024] Under inert gas, weigh A according to the stoichiometric ratio of the required general formula. x1 B x2 、M y1 B y2 、M z1 O z2 and uniformly mixing the materials to obtain a mixed material, and subjecting the mixed material to mechanical ball milling to prepare a low-carrier oxyhalide solid electrolyte material.

[0025] In the preparation method of the present invention, those skilled in the art can feed materials according to the stoichiometric ratio, that is, according to the proportional relationship between the elements of the low-carrier oxyhalide solid electrolyte material, and determine the corresponding stoichiometric ratio taking into account the losses in the feeding and preparation process.

[0026] As a further solution, the inert gas in the preparation method includes one of argon or nitrogen.

[0027] As a further solution, the parameters of the mechanical ball milling method in the preparation method are selected from the following: rotation speed: 300-600 rpm; ball milling bead diameter: 1-10 mm; ball milling bead mass: mixed material mass = (10-80): 1; ball milling time is greater than 10 h.

[0028] In a third aspect, the present invention provides a battery, comprising the low-carrier oxyhalide solid electrolyte, a positive electrode sheet, a negative electrode sheet, and a separator as described in the first aspect.

[0029] The characteristics and beneficial effects of the present invention are:

[0030] The present invention selects the oxide of a transition metal with a positive valency of tetravalent or higher as a host structure, fills the halides of the transition metal with a positive valency of tetravalent or higher and the halides of alkali metals to prepare a low-carrier oxyhalide solid electrolyte material; constructs a stable crystal framework through the oxide of the transition metal with a positive valency of tetravalent or higher; then selects the halides of the transition metal with a positive valency of tetravalent or higher and the halides of alkali metals with high compatibility with the crystal framework for collaborative filling; makes it easier for alkali metal ions to migrate in the solid electrolyte, thereby helping to improve the charge and discharge efficiency and cycle stability of the battery.

[0031] At the same time, the present invention also finely controls the constituent elements and proportions of the materials to ensure good interface compatibility between the materials, thereby reducing the diffusion barrier between the interfaces, improving mobility, and promoting structural stability during crystal growth, thereby obtaining a low-carrier oxyhalide solid electrolyte material with the same crystal structure as the host cell; the consistency of the crystal structure helps to achieve efficient transmission using fewer carriers, thereby achieving the purpose of improving ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 is the XRD diffraction pattern of Example 1 of the present invention;

[0034] Figure 2 is the XRD diffraction pattern of Example 6 of the present invention;

[0035] Figure 3 This is an electrochemical impedance test diagram of Example 1 of the present invention;

[0036] Figure 4 This is an electrochemical impedance test diagram of Example 6 of the present invention;

[0037] Figure 5 is the XRD diffraction pattern of Comparative Example 1 of the present invention;

[0038] Figure 6 It is an electrochemical impedance test diagram of comparative example 1 of the present invention. DETAILED DESCRIPTION

[0039] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.

[0040] The applicant has found that oxyhalide inorganic solid electrolytes generally have high ionic conductivity, and their electrochemical window stability and deformability are excellent, the synthesis method is simple, and they have high research and application value. In addition, the applicant has also found that high carrier concentrations in inorganic solid electrolyte materials may cause interface stability problems, increase the internal resistance of the battery, and may trigger interface side reactions, thereby affecting the battery's cycle stability and electrochemical performance. Therefore, this study is seeking a solid electrolyte material that maintains high ionic conductivity while reducing carrier concentration; and conducted the following research.

[0041] In a first aspect, the present invention provides a low-carrier oxyhalide solid electrolyte material; the material has the general formula: A a M b OB c ;0.3<a<0.7, 0.35<b<1.1, 1<c<4;

[0042] The raw materials of the material include transition metal oxide M as a host structure z1 O z2 , alkali metal halide A as filler x1 B x2 and transition metal halide M y1 B y2 ; Material A a M b OB c and the host structure M z1 O z2 have the same crystal structure;

[0043] Among them, the alkali metal A includes one or more of lithium (Li), sodium (Na), and potassium (K); M includes transition metal elements with a valence of four or more; the halogen atom B includes one or more of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); the transition metal elements with a valence of four or more include one or more of titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), hafnium (Hf), zirconium (Zr), cobalt (Co), nickel (Ni), tantalum (Ta), tungsten (W), rhenium (Re), vanadium (V), niobium (Nb), and tin (Sn).

[0044] Compared with the prior art, the preparation of inorganic solid electrolytes requires a large number of carriers to maintain the crystal structure and maintain high ion conductivity, which easily leads to high interface impedance and poor interface stability. z1 O z2 host structure, and through M y1 By2 Halides, A that forms carriers x1 B x2 As a filler composite preparation; in the preparation process, by finely controlling the constituent elements and proportions of the materials, good interface compatibility between the materials can be ensured, thereby reducing the diffusion barrier between the interfaces, improving the mobility, promoting the structural stability during the crystal growth process, and obtaining a low-carrier oxyhalide solid electrolyte material with the same crystal structure as the host cell; usually, the consistency of the crystal structure is mostly manifested as the consistency of the XRD peak during the test process, and the consistency of the XRD peak is conducive to efficient transmission using fewer carriers, thereby achieving the purpose of improving ionic conductivity.

[0045] In the process of preparing low-carrier oxyhalide solid electrolytes, the present application selects oxides of transition metals with a valency of positive tetravalent or higher as the host structure, and fills halides of transition metals with a valency of positive tetravalent or higher and halides of alkali metals to prepare low-carrier oxyhalide solid electrolyte materials; firstly, because oxides of transition metals with a valency of positive tetravalent or higher tend to have a more stable electronic configuration, it helps to form a variety of chemical bonds, so that the interaction force between the constructed structures is stronger, and a stable crystal framework can be provided, which helps to maintain the structural integrity of the entire electrolyte material, and high-valent transition metal oxides usually have larger ion channels and gaps, which are conducive to the filling of other substances, involving more electron transfer, thereby storing and releasing more energy, so that they have a higher energy density.

[0046] Secondly, after building a stable crystal framework, we selected halides of transition metals with a valence of four or above that are highly compatible with the crystal framework. They are the same as the cations of the crystal framework, which can not only further maintain the stability of the host crystal structure, but also have good interfacial compatibility during the composite process, which is beneficial to reduce the occurrence of side reactions at the interface, thereby improving mobility, reducing diffusion barriers, forming an efficient and connected ion transport channel, and optimizing the migration path and migration rate of carriers; it is beneficial to maintain a high ion conductivity while reducing the required carrier content. Thirdly, we also used alkali metal halides for collaborative filling; alkali metal ions have a lower charge density and a smaller ionic radius, which makes them easier to migrate in the solid electrolyte, thereby helping to improve the battery's charge and discharge efficiency and cycle stability; and alkali metal halides have higher thermal and chemical stability than other alkali metal compounds, and have better compatibility with halide fillers of transition metals with a valence of four or above, which helps to exist stably in the crystal structure and give full play to the ion transport performance of carriers; reduce the amount of carriers and improve structural stability.

[0047] The oxide of the transition metal with a positive valence of four or above in the host structure is filled with the halide of the transition metal with a positive valence of four or above and the halide of the alkali metal, which is conducive to maintaining the consistency of the product crystal structure and the host crystal structure; mainly because the crystal structure is highly compatible, and other crystalline phases or amorphous phases are avoided in the preparation process to affect the ion transmission rate and reduce the electrochemical application performance. The consistent crystal structure has a positive effect on the thermal stability and physical and mechanical stability of the battery, helps to reduce the lattice mismatch and stress at the interface, thereby reducing the transmission resistance of the carrier at the interface, improving the ion migration efficiency and enhancing the interface stability, so as to achieve the purpose of high-speed transmission while reducing the amount of carriers.

[0048] As a further embodiment, the A x1 B x2 、M z1 O z2 and M y1 B y2 In, x 1 、x 2 ,y 1 ,y 2 、z 1 、z 2 All are greater than 0; x 1 =x 2 .

[0049] As a further embodiment, the material A a M b OB c Preferably 1.2<b / a<2;

[0050] Furthermore, the material A a M b OB c Preferably, it is selected from the group consisting of 0.5<a<0.6, 0.75<b<0.88, 2<c<3.5, and 1.45<b / a<1.65.

[0051] Material A in the preferred range a M b OB c The element ratio ensures the formation of a stable structure in the solid electrolyte and optimizes the ion migration path. By precisely controlling the values ​​of a, b, and c, the conductivity and mechanical strength of the material can be further improved to meet the requirements of battery performance in different application scenarios. In addition, the materials within this preferred range show good chemical stability and thermal stability during the preparation process, which helps to extend the service life of the battery.

[0052] As a further embodiment, the transition metal oxide M z1 O z2 Preferred are oxides of transition metal elements containing positive pentavalent valence.

[0053] The elements within this range have stable chemical valences, and the oxides formed have more stable mechanical properties and thermal stability within a wider electrochemical window. When used with other fillers to prepare solid electrolytes, it is beneficial to reduce volume changes during lattice growth and reduce the generation of side reactions, thereby forming a consistent lattice structure; it reduces the carrier transport energy barrier and realizes the preparation of low-carrier oxyhalide solid electrolyte fillers with higher electrical conductivity.

[0054] As a further embodiment, the transition metal oxide M z1 O z2 Preferred from Ta 2 O 5 , Nb 2 O 5 One or more of; the alkali metal halide A as filler x1 B x2 Preferably, one or more of LiCl, LiF, NaCl, and LiBr; the transition metal halide M as the filler y1 B y2 Preferably TaCl 5 、NbCl 5 、TaBr 5 , NbBr 5 One or more of .

[0055] As a further solution, the low-carrier oxyhalide solid electrolyte material is selected from Li 0.53 Nb 0.4 Ta 0.4 OCl 2.53 , Li 0.53 Ta 0.8 OCl 2 Br 0.53 , Li 0.42 Ta 0.32 Zr 0.32 OCl 1.26 , Li 0.66 Ta 0.5 Zr 0.5 OCl 3.16 , Li 0.6 Tc 3.79 , Li 0.405 Ta 0.5 OCl 1.9 , Li 0.325 Ta 0.6 OCl 1.325 , Li 0.56 Ta 0.8 OCl 2.56 , Li 0.4 Ta0.7 OCl 1.9 、That 0.53 Of 0.8 OCl 1.32 、That 0.53 Of 0.8 OCl 2.53 、That 0.53 Nb 0.8 OCl 2.53 、That 0.53 Zr 0.8 OCl 2.53 、That 0.66 Of 0.5 Sn 0.5 OCl 3.16 、No 0.53 Of 0.8 OCl 2.53 、No 0.53 Nb 0.8 OCl 2.53 、No 0.53 Zr 0.8 OCl 2.53 、K 0.53 Of 0.8 OCl 2.53 、K 0.53 Nb 0.8 OCl 2.53 、K 0.53 Zr 0.8 OCl 2.53 、That 0.53 Of 0.8 OClF 2.53 、That 0.53 Nb 0.8 OClF 2.53 、That 0.53 Zr 0.8 OClF 2.53 、No 0.53 Of 0.8 OClF 2.53 、No 0.53 Nb 0.8 OClF 2.53 、No 0.53 Zr 0.8 OClF 2.53 、K 0.53 Of 0.8 OF 2.53 、K 0.53 Nb 0.8 OF 2.53 、K 0.53 Zr 0.8 OF 2.53 、That 0.53 Of0.8 OBr 2.53 , Li 0.53 Nb 0.8 OBr 2.53 , Li 0.53 Zr 0.8 OBr 2.53 、Na 0.53 Ta 0.8 OBr 2.53 、Na 0.53 Nb 0.8 OBr 2.53 、Na 0.53 Zr 0.8 OBr 2.53 , K 0.53 Ta 0.8 OBr 2.53 , K 0.53 Nb 0.8 OBr 2.53 , K 0.53 Zr 0.8 OBr 2.53 One of them.

[0056] As a further embodiment, the transition metal M is preferably selected from one or more of niobium (Nb) and tantalum (Ta).

[0057] As a further solution, the alkali metal A is preferably selected from lithium (Li) ions. Among alkali metal ions, lithium ions have a smaller ion radius and a lower migration barrier, which helps to show a higher mobility in the solid electrolyte; at the same time, lithium ions also have better electrochemical stability, so lithium ions have better performance as carriers in improving the electrochemical performance of batteries.

[0058] As a further solution, the halogen atom B is preferably selected from one or more of Cl and Br; the optimized type of halogen atom can form a stable oxyhalide structure with the transition metal M and the alkali metal A. Its ion radius has a good matching effect with the radius of the oxygen ion, which makes it easier for them to maintain the original arrangement in the crystal structure, avoiding serious lattice distortion of the crystal structure, thereby maintaining the consistency of the crystal structure; this consistency helps to maintain the stability of the electrolyte material, thereby forming a stable ion transmission channel in the solid electrolyte. In addition, the difference in electronegativity between Cl and Br can adjust the chemical stability of the solid electrolyte, so that during the battery charging and discharging process, the solid electrolyte can maintain good chemical and electrochemical stability, thereby extending the service life of the battery.

[0059] As a further embodiment, the material A a M b OB c Preferred from Li aTa b OCl c , Li a Nb b OCl c , Li a Ta b OBr c , Li a Nb b OBr c One or more of; wherein, 0.3<a<0.7, 0.35<b<1.1, 1<c<4, 1.2<b / a<2.

[0060] Materials within this range can achieve optimal coordination between crystal structure and ion migration path; they have a faster ion migration path, so that lower carriers can be used to achieve better ion conductivity, thereby improving the electrochemical performance and cycle stability of the battery.

[0061] As a further embodiment, the ionic conductivity of the material is greater than 1 mS cm -1 .

[0062] As a further solution, the mass percentage of A atoms in the material is selected from 1-3%, wherein the mass percentage refers to the total mass of A atoms in the material A. a M b OB c Ratio of total mass.

[0063] Furthermore, the mass percentage of A atoms in the material is preferably 1-1.5%.

[0064] The mass percentage of A atoms in the present application can ensure that a higher ion migration capacity is provided while maintaining a low carrier content; avoid excessively high carrier content, which may lead to a crowding effect in the electrolyte and hinder the movement of ions; and avoid the possible increase in resistance and serious problems of dendrite growth.

[0065] In a second aspect, the present invention provides a method for preparing a low-carrier oxyhalide solid electrolyte material; the preparation method comprises:

[0066] Under inert gas, weigh A according to the stoichiometric ratio of the required general formula. x1 B x2 、M y1 B y2 、M z1 O z2 and uniformly mixing the materials to obtain a mixed material, and subjecting the mixed material to mechanical ball milling to prepare a low-carrier oxyhalide solid electrolyte material.

[0067] In the preparation method of the present invention, those skilled in the art can feed materials according to the stoichiometric ratio, that is, according to the proportional relationship between the elements of the low-carrier oxyhalide solid electrolyte material, and determine the corresponding stoichiometric ratio taking into account the losses in the feeding and preparation process.

[0068] As a further solution, the inert gas in the preparation method includes one of argon or nitrogen.

[0069] As a further solution, the parameters of the mechanical ball milling method in the preparation method are selected from the following: rotation speed: 300-600 rpm; ball milling bead diameter: 1-10 mm; ball milling bead mass: mixed material mass = (10-80): 1; ball milling time is greater than 10 h.

[0070] In a third aspect, the present invention provides a battery, comprising the low-carrier oxyhalide solid electrolyte, a positive electrode sheet, a negative electrode sheet, and a separator as described in the first aspect.

[0071] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0072] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0073] Example 1

[0074] Li 0.53 Ta 0.8 OCl 2.53 Preparation: LiCl and Ta were weighed in a nitrogen atmosphere according to the stoichiometric ratio of the general formula. 2 O 5 With TaCl 5 and mix the above materials evenly; then, the mixed powder is subjected to high-energy ball milling (ball milling bead diameter 5 mm, ball milling bead mass: mixed material mass = 30:1) at a rotation speed of 500 rpm (revolutions per minute) in a nitrogen atmosphere for 20 hours to obtain a low-carrier oxyhalide solid electrolyte.

[0075] Example 2

[0076] The specific steps and preparation method are the same as those in Example 1, except that: 0.53 Nb 0.4 Ta 0.4 OCl2.53 : Under inert gas, weigh LiCl and Ta according to the stoichiometric ratio of the general formula. 2 O 5 With NbCl 5 , and mix the above materials evenly.

[0077] Example 3

[0078] The specific steps and preparation method are the same as those in Example 1, except that: 0.53 Ta 0.8 OCl 2 Br 0.53 : Under inert gas, weigh LiBr and Ta according to the stoichiometric ratio of the general formula. 2 O 5 With TaCl 5 , and mix the above materials evenly.

[0079] Example 4

[0080] The specific steps and preparation method are the same as those in Example 1, except that: 0.53 Nb 0.4 Ta 0.4 OCl 2.53 : Under inert gas, weigh LiCl and Nb according to the stoichiometric ratio of the general formula. 2 O 5 With TaCl 5 , and mix the above materials evenly.

[0081] Example 5

[0082] The specific steps and preparation method are the same as those in Example 1, except that: 0.42 Ta 0.32 Zr 0.32 OCl 1.26 Under inert gas, weigh LiCl and ZrCl according to the stoichiometric ratio of the general formula. 4 With Ta 2 O 5 , and mix the above materials evenly.

[0083] Example 6

[0084] The specific steps and preparation method are the same as those in Example 1, except that: 0.53 Ta 0.8 OCl 2.53 ; Under inert gas, weigh NaCl and Ta according to the general stoichiometric ratio. 2 O 5 With TaCl 5 , and mix the above materials evenly.

[0085] Example 7

[0086] The specific steps and preparation method are the same as those in Example 1, except that: 0.66 Ta 0.5 Zr 0.5 OCl 3.16 ; Under inert gas, weigh LiCl and ZrO according to the stoichiometric ratio of the general formula 2 With TaCl 5 , and mix the above materials evenly.

[0087] Example 8

[0088] The specific steps and preparation method are the same as those in Example 1, except that: 0.66 Ta 0.5 Sn 0.5 OCl 3.16 ;; Under inert gas, weigh LiCl and SnO according to the stoichiometric ratio of the general formula 2 With TaCl 5 , and mix the above materials evenly.

[0089] Example 9

[0090] The specific steps and preparation method are the same as those in Example 1, except that: 0.6 Tc 3.79 ; Under inert gas, weigh LiCl and Ta according to the stoichiometric ratio of the general formula 2 O 5 With TaCl 5 , and mix the above materials evenly.

[0091] Comparative Example 1

[0092] The specific steps and preparation method are the same as those in Example 1, except that: 0.88 Ta 0.66 Sb 0.66 OCl 4.21 ; Under inert gas, weigh LiCl and Sb according to the stoichiometric ratio of the general formula 2 O 3 With TaCl 5 , and mix the above materials evenly.

[0093] Comparative Example 2

[0094] The specific steps and preparation method are the same as those in Example 1, except that: 2.17 Ta 2 OCl 10.16 ; Under inert gas, weigh LiCl and Ta according to the stoichiometric ratio of the general formula 2 O 5 With TaCl 5, and mix the above materials evenly.

[0095] Comparative Example 3

[0096] Li 0.3 Ta 0.4 Cl 2.53 Preparation: LiCl and TaCl were weighed in a nitrogen atmosphere according to the stoichiometric ratio of the general formula. 5 and mix the above materials evenly; then, the mixed powder is subjected to high-energy ball milling (ball milling bead diameter 5 mm, ball milling bead mass: mixed material mass = 30:1) at a rotation speed of 500 rpm (revolutions per minute) under a nitrogen atmosphere for 20 hours to obtain a solid electrolyte.

[0097] Comparative Example 4

[0098] Li 0.3 Ta 0.4 Cl 2.53 Preparation: LiCl and TaCl were weighed in a nitrogen atmosphere according to the stoichiometric ratio of the general formula. 5 and mix the above materials evenly; then, the mixed powder is subjected to high-energy ball milling (ball milling bead diameter 5 mm, ball milling bead mass: mixed material mass = 30:1) at a rotation speed of 500 rpm (revolutions per minute) under a nitrogen atmosphere for 40 hours to obtain a solid electrolyte.

[0099] Specific test methods and conditions:

[0100] 130 mg of electrolyte powder was placed in a custom test cell mold with a diameter of 10 mm, with stainless steel as the blocking electrode, and a pressure of 380 MPa was applied for tableting. The electrochemical impedance information was tested using an SP-300 (Bio-logic) electrochemical workstation. The ionic conductivity was calculated using the electrochemical impedance spectroscopy test according to the formula (σ = L / RA, L is the thickness of the solid electrolyte, R is the resistance of the electrochemical impedance spectroscopy test, and A is the area).

[0101] Table 1

[0102]

[0103]

[0104] It can be seen from the data in Table 1 and the examples and comparative examples that the oxyhalide solid electrolyte material prepared in Table 1 has a lower carrier content, a higher ionic conductivity and a lower interface impedance than the oxyhalide solid electrolyte material obtained in the comparative example, and exhibits better electrochemical performance in battery applications; in addition, Figure 1 , Figure 2It can also be seen that the low-carrier oxyhalide solid electrolyte material prepared in the embodiment has consistent XRD diffraction peaks with its transition metal oxide host structure, indicating that the lattice structure is consistent during the preparation process, thereby obtaining a lower interface impedance and having an efficient carrier transmission path, thereby achieving the effect of using lower carriers to obtain higher electrical performance improvement.

[0105] It can be seen from Example 1 and Comparative Examples 1 and 2 that when the prepared solid electrolyte material is not within the optimization range of the present application, its ionic conductivity and impedance do not have a better range relative to the embodiment. Figure 5 The prepared solid electrolyte material is not consistent with the X-ray diffraction peak of the host structure transition metal oxide; it indicates that the crystal structure of the solid electrolyte product has changed during the preparation process. During the filling process, the lattice change inconsistent with the host structure will cause the interface impedance to be too high, hindering the ion migration path, and failing to effectively improve the ion conductivity, which easily leads to instability of the electrochemical performance. The solid electrolyte material prepared in Example 1 according to the optimized range of the present invention has an X-ray diffraction peak that is consistent with the host structure transition metal oxide, indicating that it has a stable crystal structure, thereby ensuring the ion migration rate and electrochemical stability of the battery.

[0106] It can be seen from Example 1 and Comparative Examples 3 and 4 that, in the preparation process of the solid electrolyte material, without adding transition metal oxides to construct the host structure, the ionic conductivity and electrochemical impedance are poor, indicating that constructing a host structure with consistent XRD derivative peaks helps to improve the ionic conductivity of the material.

[0107] It can be seen from Examples 1-4 and 5-9 that the solid electrolyte materials within the preferred element content and element ratio range show excellent ionic conductivity and low interface impedance in the electrochemical performance test. And Examples 5-9 further confirm that when the type, content, and element ratio of the raw materials used to prepare the solid electrolyte of the present invention vary within a certain range, the electrochemical performance of the solid electrolyte material remains stable, which indicates that the solid electrolyte material prepared in the embodiment of the present invention achieves low carrier concentration and high ion conductivity; and the prepared solid electrolyte material has high electrochemical performance in the electrochemical performance test of the battery.

[0108] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-carrier oxyhalide solid electrolyte material; the material has the general formula: A a M b OB c ;0.3<a<0.7, 0.35<b<1.1, 1<c<4; The raw materials of the material include transition metal oxide M as a host structure z1 O z2 , alkali metal halide A as filler x1 B x2 and transition metal halide M y1 B y2 ; Material A a M b OB c and the host structure M z1 O z2 have the same crystal structure; in, Alkali metal A includes one or more of lithium (Li), sodium (Na), and potassium (K); M includes transition metal elements with a positive valence of tetravalent or higher; halogen atom B includes one or more of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); transition metal elements with a positive valence of tetravalent or higher include one or more of titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), niobium (Nb), molybdenum (Mo), ruthenium (Ru), rhodium (Rh), palladium (Pd), hafnium (Hf), zirconium (Zr), cobalt (Co), nickel (Ni), tantalum (Ta), tungsten (W), rhenium (Re), vanadium (V), niobium (Nb), and tin (Sn).

2. The low-carrier oxyhalide solid electrolyte material according to claim 1, characterized in that: The A x1 B x2 、M z1 O z2 and M y1 B y2 In the equation, x1, x2, y1, y2, z1, z2 are all greater than 0; x1 = x2; The material A a M b OB c Preferably 1.2<b / a<2; Furthermore, the material A a M b OB c Preferably, it is selected from the group consisting of 0.5<a<0.6, 0.75<b<0.88, 2<c<3.5, and 1.45<b / a<1.

65.

3. The low-carrier oxyhalide solid electrolyte material according to claim 1, characterized in that: The transition metal oxide M z1 O z2 Preferably, the oxide is selected from the group consisting of transition metal elements having a positive pentavalent valence; Furthermore, the transition metal oxide M z1 O z2 Preferably, one or more of Ta2O5 and Nb2O5; the alkali metal halide A as filler x1 B x2 Preferably, one or more of LiCl, LiF, NaCl, and LiBr; the transition metal halide M as the filler y1 B y2 Preferably one or more of TaCl5, NbCl5, TaBr5, NbBr5.

4. The low-carrier oxyhalide solid electrolyte material according to claim 1, characterized in that: The low-carrier oxyhalide solid electrolyte material is selected from Li 0.53 Nb 0.4 Ta 0.4 OCl 2.53 , Li 0.53 Ta 0.8 OCl2Br 0.53 , Li 0.42 Ta 0.32 Zr 0.32 OCl 1.26 , Li 0.66 Ta 0.5 Zr 0.5 OCl 3.16 , Li 0.6 Tc 3.79 , Li 0.405 Ta 0.5 OCl 1.9 , Li 0.325 Ta 0.6 OCl 1.325 , Li 0.56 Ta 0.8 OCl 2.56 , Li 0.4 Ta 0.7 OCl 1.9 , Li 0.53 Ta 0.8 OCl 1.32 , Li 0.53 Ta 0.8 OCl 2.53 , Li 0.53 Nb 0.8 OCl 2.53 , Li 0.53 Zr 0.8 OCl 2.53 , Li 0.66 Ta 0.5 Sn 0.5 OCl 3.16 、Na 0.53 Ta 0.8 OCl 2.53 、Na 0.53 Nb 0.8 OCl 2.53 、Na 0.53 Zr 0.8 OCl 2.53 , K 0.53 Ta 0.8 OCl 2.53 , K 0.53 Nb 0.8 OCl 2.53 , K 0.53 Zr 0.8 OCl 2.53 , Li 0.53 , Ta 0.8 , OClF 2.53 , Li 0.53 , Nb 0.8 , OClF 2.53 , Li 0.53 , Zr 0.8 , OClF 2.53 , Na 0.53 , Ta 0.8 , OClF 2.53 , Na 0.53 , Nb 0.8 , OClF 2.53 , Na 0.53 , Zr 0.8 , OClF 2.53 , K 0.53 , Ta 0.8 , OF 2.53 , K 0.53 , Nb 0.8 , OF 2.53 , K 0.53 , Zr 0.8 , OF 2.53 , Li 0.53 , Ta 0.8 , OBr 2.53 , Li 0.53 , Nb 0.8 , OBr 2.53 , Li 0.53 , Zr 0.8 , OBr 2.53 , Na 0.53 , Ta 0.8 , OBr 2.53 , Na 0.53 , Nb 0.8 , OBr 2.53 , Na 0.53 , Zr 0.8 , OBr 2.53 , K 0.53 , Ta 0.8 , OBr 2.53 , K 0.53 , Nb 0.8 , OBr 2.53 , K 0.53 , Zr 0.8 , OBr 2.53 among them.

5. The low-carrier oxyhalide solid electrolyte material according to claim 1, characterized in that: The transition metal M is preferably one or more selected from niobium (Nb) and tantalum (Ta); Furthermore, the halogen atom B is preferably one or more selected from Cl, Br; Furthermore, the alkali metal A is preferably selected from lithium (Li) ions.

6. The low-carrier oxyhalide solid electrolyte material according to claim 1, characterized in that: The material A a M b OB c Preferred from Li a Ta b OCl c , Li a Nb b OCl c , Li a Ta b OBr c , Li a Nb b OBr c One or more of; wherein, 0.3<a<0.7, 0.35<b<1.1, 1<c<4, 1.2<b / a<2.

7. The low-carrier oxyhalide solid electrolyte material according to claim 1, characterized in that: The ionic conductivity of the material is greater than 1 mS cm -1 ; The mass percentage of A atoms in the material is selected from 1-3%, wherein the mass percentage refers to the total mass of A atoms in the material A. a M b OB c proportion of total mass; Furthermore, the mass percentage of A atoms in the material is preferably 1-1.5%.

8. A method for preparing a low-carrier oxyhalide solid electrolyte material; the preparation method comprising: Under inert gas, weigh A according to the stoichiometric ratio of the required general formula. x1 B x2 、M y1 B y2 、M z1 O z2 and uniformly mixing the materials to obtain a mixed material, and subjecting the mixed material to mechanical ball milling to prepare a low-carrier oxyhalide solid electrolyte material.

9. The preparation method according to claim 8, characterized in that: In the preparation method, the inert gas includes one of argon or nitrogen; The parameters of the mechanical ball milling method in the preparation method are selected from the following: rotation speed: 300-600 rpm; ball milling bead diameter: 1-10 mm; ball milling bead mass: mixed material mass = (10-80): 1; ball milling time is greater than 10 hours.

10. A battery, comprising the low-carrier oxyhalide solid electrolyte according to any one of claims 1 to 7, a positive electrode sheet, a negative electrode sheet, and a separator.

Citation Information

Patent Citations

  • Halide solid electrolyte and preparation method thereof

    CN116960441A

  • Sodium ion halide solid electrolyte, preparation method and all-solid-state sodium ion battery

    CN118016986A

  • Oxidation halide solid electrolyte and preparation method and application thereof

    CN118336096A

  • Oxidation halide solid electrolyte and preparation method and application thereof

    CN118748268A

Cited By

  • Niobium-based solid electrolyte and preparation method and application thereof

    CN120199881A

  • Oxygen halide solid electrolyte material and preparation method and application thereof

    CN121377106A